Obsessive beliefs in generalized anxiety disorder - Guliz Senormanci; Ramazan Konkan; Omer Senormanci (Bilişsel Davranışçı Psikoterapi ve Araştırmalar Dergisi)
Several studies have shown that obsessive beliefs are not specific for OCD, may also play a role in occurence of other anxiety disorders and depression. In these studies, anxiety disorders were evaluated together, with mixed samples of anxiety disorders. Obsessive beliefs are assessed in a sample of generalized anxiety disorder (GAD) and compared with healthy control group. The current study compared 119 patients with GAD and 137 healthy controls. Written informed consent was provided and Obsessive Beliefs Questionnaire-44 (OBQ-44), Generalized Anxiety Disorder-7 (GAD-7) scale, Beck Depression Inventory (BDE), State-Trait Anxiety Inventory (STAI) were administered to each participant. Total scores and subscale scores for OBQ-44 in the GAD group were found to be significantly higher the control group (p0,05) except perfectionism/intolerance of uncertainty subscale (p=0,000). According to of our study, perfectionism/intolerance of uncertainty continues to be statistically significant when state anxiety, trait anxiety and depression levels were controlled respectively. The perfectionism/intolerance of uncertainty may contribute to development and persistence of GAD symptoms and evaluation and development of approaches to change these beliefs may improve results of cognitive behavioral therapy in GAD patients. [JCBPR 2017; 6(3.000): 115-122]